The impact of massclusivity campaigns on perceptions and brand love of Gucci online brand communities’ members - Bilro, R. G. (2019)
The current research aims to understand the impact of Massclusivity (massive and exclusive) campaigns on the brand love through online brand communities (OBC) interactions. Authors designed a netnography research with the purpose of analysing the interactions between a brand - the luxury fashion brand Gucci – and its online brand community on Facebook, during a specific period of time defined according to the launch of a Massclusivity campaigns of this brand. We collect a total of 10,689 interactions from March 2017 to March 2018. Findings highlight that the development of massclusivity campaigns have several impacts, such as generate awareness towards the brand, increases consumers’ engagement on SNP, and promotes communities’ expansion. These are directly connected to the interest that this type of marketing strategies generates towards the brands, which may be considered powerful to luxury brands who intend to diversify their audience and become more competitive.